PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Utami, Siska Widia (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2019)
The purpose of this study was to examine the influence of the Good Corporate Governance on Corporate Social Responsibility Disclosure with Profitability and Leverage as control variables. Data analysis technique used in this research is multiple regression linear analysis. This research use causality method. The population in this study are all manufacturing companies are listed on Indonesia Stock Exchange in 2016-2017. The data chosen using random sampling method. Total sample in this research as many as 60 companies. The results showed that: (1) Institutional Ownership has no significant effect on the Corporate Social Responsibility Disclosure. (2) Foreign Ownership has significant effect on the Corporate Social Responsibility Disclosure. (3) Competence of Independent Commissioners Board has no significant effect on the Corporate Social Responsibility Disclosure. (4) Competence of Audit Committe has no significant effect on the Corporate Social Responsibility Disclosure.